All too well versus uptown funk: an indirect theory of mind replication using writerly and readerly song lyrics in a plurilingual setting / Siti Auji Ashari - Ahari, Siti Auji (Universiti Teknologi MARA (UiTM), 2023)
The theory of mind, at its core, concerns the emotional intelligence, our empathy, and the ability to read and interpret the mental states of others we interact with. In the early 2010s, Kidd and Castano (2013) carried out a seminal re- search to investigate the theory of mind effects of reading literary fiction versus reading popular genre fiction, nonfiction, and no reading. The researchers found that the former enhanced the performance in the theory of mind test, namely the Reading the Mind in the Eyes Test (RMET), more than the latter three did. Consequently, the original re- searchers encouraged the replications of their research, either directly or indirectly using other media. The present paper reports on one such replication, using song lyrics as the indirect medium. Conducted with 29 undergraduate medical students at plurilingual UCSI University Terengganu Campus, the results show that the writerly All Too Well group performed the best in the RMET, whereas there was no significant difference in the RMET performance be- tween the readerly Uptown Funk group and the control group. For this study, therefore, the theory of mind effects were positive only for the writerly texts, but not for the readerly. Accordingly, this paper calls for more future replications, especially indirectly using media other than book excerpts, on the theory of mind effects.